PENGARUH LOAN TO DEPOSIT RATIO, FIRM SIZE, DAN EQUITY TO TOTAL ASSET RATIO TERHADAP RETURN ON ASSET PADA PT. BANK RAKYAT INDONESIA (PERSERO) TBK. PERIODE 2008-2015 - Eka Susilowati; Ahmadi Ahmadi; Yunan Surono (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2017)
Loan total development during the last eight years fluctuated by an average of 0.202%. Developments in total deposits during the last eight years with an average of 0.099%. Development Total Assets for eight years with an average of 0.202%. Total Equity developments over the last eight years with an average of 0.263% .And pekembangan Return On Asset PT. Bank Rakyat Indonesia (persero)  Tbk during the last eight years with an average of 0.007%. The higher the loan to deposit ratio of the low liquidity of the bank concerned, the standard large loan to deposit ratio. Determinants of the size of the company is based in total assets of the company, a large company that has a large total assets that can generate income. Equity to Total Assets Ratio as an indicator of the role of the owner or shareholder of the increased efficiency and viability of the business of the bank in question is the proportion of equity capital to total assets of the bank. Variables simultaneously Loan to Deposit Ratio (X1), Firm Size (X2), and Equity to Total Assets Ratio simultaneously have a significant effect on the dependent variable (Y) at PT. Bank Rakyat Indonesia (persero)  Tbk period 2008-2015. in partial Loan to Deposit Ratio (LDR) significantly affects the Return On Asset, Firm Size variable and Equity to Total Assets Ratio no significant effect on return on assets And the PT. Bank Rakyat Indonesia (pesero) Tbk period 2008-2015. Keyword: loan to deposito rasio, firm size, equity to total asset ratio